Stavebně technologický projekt objektů posklizňové linky - Bahulíková, Pavla (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem diplomové práce je soubor objektů posklizňové linky v obci Horní Moštěnice u města Přerov. Diplomová práce řeší pro celou stavbu časový plán, společně s finančním plánem. Ve výkresu zařízení staveniště je řešeno založení celé stavby. Dále je to technická zpráva, stavebně technologická studie a hluková studie. Práce je zaměřena na skladovací sila, pro něž je zpracován podrobný časový plán, rozpočet, návrh strojní sestavy, technologický předpis pro montáž sil, zásady organizace výstavby, technická zpráva zařízení staveniště, kontrolní a zkušební plán, bezpečnost a ochrana zdraví při práci a staveništní hluk.

The topic of this thesis is a collection of objects of the postharvest line in the village Horní Moštěnice by the town Přerov. The thesis resolves the time schedule along with the financial plan. In the drawing of the constructional plant is being solved the establishment of the whole construction. Further is it the technical report, site engineering study and a noise study. The thesis is focused on the storage bins, for which is being developed a detailed time schedule, a budget, a drawing of the machine configuration, a technological standard for the assembly of the storage bins, the principles for the construction management, technical management of the constructional plant, control and test plan, safety and health at work protection and the construction site noise.
Construction technological project of objects harvest lines
Keywords: Posklizňová linka; montáž ocelové konstrukce; časový plán; rozpočet; kontrolní a zkušební plán; bezpečnost práce; hygienické limity hluku.; Postharvest line; structural steel erection; time schedule; budget; control and test plan; work safety; sanitary noise limits.